Spectrum of cardiovascular manifestations in homozygous familial hypercholesterolemia - Nitin Bajaj; Balbir Singh; Ananthkrishnan Ramamoorthy; Arijit Kumar Ghosh (Journal of Marine Medical Society, 2023)
Homozygous familial hypercholesterolemia (HoFH) is a rare, primarily an autosomal dominant genetic disorder that causes markedly elevated low-density lipoprotein (LDL) cholesterol levels predisposing patients to risk of developing premature atherosclerotic cardiovascular diseases. Disease manifestations usually develop in 1st or 2nd decade of life and severity depends on the duration of exposure to elevated LDL cholesterol levels. The mainstay in management is early recognition and treatment with various lipid-lowering agents including lipid-apheresis in severe cases not responding to drug therapy. We report three cases of HoFH presenting to our institute in their 2nd decade of life with different cutaneous and cardiovascular manifestations and discuss challenges in their management.